THE EFFECT OF LEVERAGE, CAPITAL INTENSITY, AND INVENTORY INTENSITY ON EFFECTIVE TAX RATE - Utami, Rini; Mahpudin, Endang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.01.TAHUN. 2021DO - 10.24843/EEB.2021.v10.i01.p01, 2021)
This study aims to determine the effect of leverage, capital intensity and inventory intensity on effective tax rate on miscellaneous industry sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The method used is descriptive statistics with quantitative approach that is through the classical assumption test to analyze the data and multiple linear regression analysis and processed by using software SPSS 20. While data used are secondary data with quantitative data types during the period 2014 until 2018. Population of this study is the miscellaneous industry sector manufacturing companies with sampling method that is purposive sampling, so that the number of observations obtained as many as 12 companies. Simultaneously results test show that leverage, capital intensity and inventory intensity simultaneously affect effective tax rate. And partially, leverage and capital intensity has an effect on effective tax rate However inventory intensity partially does not have an effect on effective tax rate.